Prognostic follow-up of high-grade squamous intraepithelial lesions of the cervix near the conization margin: A retrospective cohort study - Dandan Chen; Huamin Wu; Feifeng Huang; Kailiang Tan (PLoS ONE, 2025)
Objective This study explored the prognosis of high-grade squamous intraepithelial lesion (HSIL) patients with negative margins, investigating the impact of different distances between lesions and incisal margins in conization specimens. Methods This retrospective cohort study included 240 HSIL patients. Patients with negative incisal margins were divided into 3 groups according to the distance between the lesion and the incisal margin in the conization tissue. Group 1 consisted of a distance of <1 mm (n = 23), Group 2 of 1–3 mm (n = 15), and Group 3 of >3 mm (n = 202). For patients with lesions close to the incisal margin (≤3 cm), the decision between total hysterectomy and clinical observation was made based on patient preference following detailed counseling of disease characteristics and prognosis. Thinprep cytologic test (TCT) and HPV testing were performed during follow-up at 6 and 12 months after the operation. Results No significant difference in HPV and TCT positive rate was observed among the three groups at 6 months and 12 months after the operation (P = 0.561, 0.561 and P = 0.324, 0.268). In the group with a distance shorter than 3 mm, no difference in HPV positive rate was found between the total hysterectomy and observation groups (P = 0.480, 0.737). Additionally, no difference in HPV positive rate was observed between patients who underwent total hysterectomy compared to clinical observation in groups 1 and 2 (P = 0.565, 0.692; P = 0.758, 0.593). Stratified analysis revealed that HPV positive rates at 6 months and 12 months had no statistical significance with any factor. Conclusion Different distances between conization tissue lesions and incisal edges have no direct impact on the prognosis of HSIL patients with negative conization biopsy tissues; excessive hysterectomy is not recommended in patients (≤3 mm) close to incisal edges.